Brain-derived neurotrophic factor is increased in serum levels of patients with symptomatic dermographism - Erpolat, Seval; Celik, Huseyin Tugrul; Bozkurt, Bulent (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Symptomatic dermographism (SD) is the most common form of physical urticaria. However, the role of neuroimmune mechanisms in SD is unclear. Aim: To investigate circulating levels of brain-derived neurotrophic factor (BDNF) in symptomatic dermographism. Material and methods: Thirty-two patients suffering from SD and 33 healthy subjects were included in the study. Serum BDNF levels were determined by a human enzyme-linked immunoassay (ELISA) kit. The serum C-reactive protein concentration and eosinophil counts in peripheral blood were evaluated. Results: The BDNF serum levels were detectable in both SD patients and healthy controls. The BDNF serum levels were significantly higher in patients with SD compared with healthy controls (p = 0.004). There was a positive but weak correlation between serum BDNF and CRP levels; it was not statistically significant (r = 0.211, p = 0.255). There was also a positive but weak correlation between serum BDNF and eosinophil counts; it was not statistically significant (r = 0.271, p = 0.141). Conclusions: The present study shows that BDNF is increased in the serum levels of patients with SD, suggesting a role for BDNF in the pathophysiology of this disorder.